A Comparison of General and Work‐specific Personality Measures as Predictors of Organizational Citizenship Behavior. (June 2016) - Wang, Qiang; Bowling, Nathan A.
Abstract : The current study compared general and work‐specific measures of personality as predictors of organizational citizenship behavior (OCB). Consistent with the literature on frame‐of‐reference effects in personality assessment, two of the Five Factor Model dimensions – agreeableness and conscientiousness – were significantly related to OCB. Use of a frame of reference that is conceptually relevant to the criterion led to increased validity as a result of the decrement in between‐subject variability and within‐subject inconsistency. Results indicated that work‐specific personality yielded significant incremental relationships with OCB even after general personality is controlled. Finally, regression analyses found that the incremental variance predicted by work‐specific personality decreased as the degree of between‐subject variability and within‐subject inconsistency increased. Overall, the results suggest that there are benefits to considering the work‐specific measure of personality in the prediction of OCB.